2014
DOI: 10.1136/amiajnl-2013-002454
|View full text |Cite
|
Sign up to set email alerts
|

A patient-centered longitudinal care plan: vision versus reality

Abstract: The use of LCPs to support care transitions is suboptimal. Strategies are needed to transform the LCP from vision to reality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 29 publications
3
45
0
Order By: Relevance
“…Limitations include: inability to generate population-based reports easily; problems in presenting usable alerts and reminders; inability to capture data on preventive care; and non-interoperability between different EHR systems [ 2 ]. In addition, longitudinal care plans are not used [ 12 ] and while systems may be able to alert providers about gaps in care, they do not link to relevant clinical patient data [ 29 ].…”
Section: Medical Home Technologies and Phmmentioning
confidence: 99%
“…Limitations include: inability to generate population-based reports easily; problems in presenting usable alerts and reminders; inability to capture data on preventive care; and non-interoperability between different EHR systems [ 2 ]. In addition, longitudinal care plans are not used [ 12 ] and while systems may be able to alert providers about gaps in care, they do not link to relevant clinical patient data [ 29 ].…”
Section: Medical Home Technologies and Phmmentioning
confidence: 99%
“…Additionally, although small studies have demonstrated the benefit of EMR-based ECP tools,4 in practice, ECPs are not typically used in the ambulatory setting and significant ambiguity exists regarding what constitutes care planning 3. Where longitudinal ECPs exist, they are often not standardized or interdisciplinary in nature and are variably found in electronic format 5. And while care planning and coordination are of significant interest to commercial vendors, commercial tools are more commonly used for data aggregation and identification of high-risk populations and overdue interventions rather than for workflow coordination or communication enhancement capabilities 6…”
Section: Introductionmentioning
confidence: 99%
“…10 In regard to professional behavior, studies also stress that failures in communication when delivering care and problems with the content and reliability of information transferred through different settings have been identified as threats to patient safety. 11 The services provided within the field of nursing play an important role in the search for quality in healthcare organizations, given the number of professionals working in these institutions and their responsibility in providing 24-hour care. 12 The combination of nursing competencies and training can be linked to the evolution of patients' conditions.…”
Section: Introductionmentioning
confidence: 99%